Zakat And Economic Growth: Islamic Economic Perspective - Gojali, Dudang; Yakubi, Yusef; Setiawan, Iwan; Zaky, Muhammad; Rahmah, Yulia Fithriany (Journal of Islamic Economics and Business, 2024)
Poverty and unemployment in Indonesia are currently problems of economic growth that are difficult to solve due to the unequal and unequal distribution of wealth or income among individuals in society itself. The existence of zakat is an important role in overcoming this. However, the zakat instrument is still felt to be less than optimal. The purpose of this writing is to examine the role of zakat in economic growth from an Islamic economic perspective, as well as study the challenges and opportunities in managing zakat, especially in the modern era. The research method used in this research is descriptive analysis with a qualitative approach. The results of the research show that zakat plays an important role in economic growth according to an Islamic economic perspective. Economic growth is measured through an increase in per capita income, a decrease in unemployment, and a decrease in poverty. As an Islamic economic instrument, zakat helps achieve these indicators by ensuring a more equitable distribution of income and poverty alleviation.